2014
DOI: 10.1088/0953-8984/26/21/216001
|View full text |Cite
|
Sign up to set email alerts
|

EuNiGe3, an anisotropic antiferromagnet

Abstract: Single crystals of EuNiGe3, crystallizing in the non-centrosymmetric BaNiSn3-type structure, were grown using In flux, enabling us to explore the anisotropic magnetic properties, which was not possible with previously reported polycrystalline samples. The EuNiGe3 single crystalline sample is found to order antiferromagnetically at 13.2 K, as revealed from the magnetic susceptibility, heat capacity and electrical resistivity data. The low temperature magnetization M (H) is distinctly different for the field par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 12 publications
11
63
2
Order By: Relevance
“…Figure 4 top shows that, up to 12 K, the thermal variation of the scattering intensity can be well fitted to the S=7/2 mean field function adequate for Eu 2+ ions, with a molecular field constant |λ| 5.95 T/µ B . Such a fit gives an excellent agreement between calculated and experimental data, with a transition tem- perature T t 12.0 K. Above 11 K, the (1+δ 1 /4 1) satellite intensity deviates from the mean field function, and vanishes above 13.5 K. In this temperature range, the observed small shift of the δ value corresponds to the intermediate phase reported in the Mössbauer investigation 15 , which shows an incommensurate modulation of Eu moments. Therefore, the value δ =0.066 does correspond to an incommensurate modulation, but the weakness of the magnetic signal in this phase prevented us from determining its detailed structure.…”
Section: The Magnetic Structure In Zero Fieldsupporting
confidence: 73%
See 2 more Smart Citations
“…Figure 4 top shows that, up to 12 K, the thermal variation of the scattering intensity can be well fitted to the S=7/2 mean field function adequate for Eu 2+ ions, with a molecular field constant |λ| 5.95 T/µ B . Such a fit gives an excellent agreement between calculated and experimental data, with a transition tem- perature T t 12.0 K. Above 11 K, the (1+δ 1 /4 1) satellite intensity deviates from the mean field function, and vanishes above 13.5 K. In this temperature range, the observed small shift of the δ value corresponds to the intermediate phase reported in the Mössbauer investigation 15 , which shows an incommensurate modulation of Eu moments. Therefore, the value δ =0.066 does correspond to an incommensurate modulation, but the weakness of the magnetic signal in this phase prevented us from determining its detailed structure.…”
Section: The Magnetic Structure In Zero Fieldsupporting
confidence: 73%
“…15. For the neutron diffraction study, a 3x3.7x1 mm 3 single crystal was mounted with the c axis or the b axis vertical in the variable temperature insert of a 7.5 T split-coil cryomagnet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 While very similar concerns about the magnetic order parameters in antiferromagnetics were raised by Gschneidner et al, 44 treating the measured magnetization as the primary order parameter is frequently used in the magnetocaloric community. [45][46][47][48][49][50][51][52] It seems that the indirect method might still yield reasonable estimations about direct measurement results. For instance, it was reported that the direct measurement results in FeRh compounds can be well reproduced by the indirect method based on the magnetization measurements.…”
Section: Negative Electrocaloric Effect In Antiferroelectricsmentioning
confidence: 99%
“…In the rst literature report [10], based on polycrystalline data, the compound was described as a simple A-type collinear antiferromagnet with T N = 13.6 K. However, in the most recent study on single crystals [11] In this contribution, we report on the low-temperature physical behaviours in the two novel representatives of the EuTGe 3 series, namely EuCoGe 3 and EuRhGe 3 .…”
Section: Introductionmentioning
confidence: 97%